FEEDING HABITS OF THE COMMOM DOLPHINFISH Coryphaena hippurus, IN NORTHEASTERN BRAZIL’S EXCLUSIVE ECONOMIC ZONE - Júnior, Teodoro Vaske; Lessa, Rosângela Paula (Arquivos de Ciências do Mar, 2017)
Feeding habits of the commom dolphinfish, Coryphaena hippurus were analyzed from stomach contents of 272 fish. Samples from longline tuna fishing of the Notheastern Brazilian Exclusive Economic Zone, were colected between October, 1992 and December, 1999. The diet comprised 23 taxa of fishes, 13 cephalopods, 8 crustaceans and 1 heteropod. According to the Index of Relative Importance (IRI), fishes were the main food item, particularly young, Dactylopterus volitans, Brama brama, Cypselurus sp., and Balistes sp. Dolphinfish feed on small specimens of epipelagic organisms (1 to 7 cm), continuosly throughout the day. There is no correlation between dolphinfish body length and prey length or the weight of the stomach content.